Distributed algorithms for cooperative routing and power allocation in wireless sensor networks - SI Jiang-bo; LI Zan; DANG Lan-jun; LIU Zeng-ji (Tongxin xuebao)
Based on the optimal power allocation in cooperative transmission, two distributed algorithms, distributed separate route and power allocation algorithm （D-SRPA） and distributed joint route and power allocation algorithm （D-JRPA）, were proposed. The two algorithms combining the PHY （physical layer） and MAC （media-access control） protocol can get the similar performance as the corresponding centralized algorithms. Simulation results show that com- pared with D-JRPA, D-SRPA can save the total transmission power more efficiently.